Pengaruh Penerapan Good Corporate Governance Terhadap Kinerja Keuangan - Susana Peni Teluma; Nugraeni Nugraeni (Jurnal Akuntan Publik, 2025)
This research aims to test and analyze the influence of good corporate governance on company financial performance. Good corporate governance in this research is proxied by the percentage of institutional ownership, composition of the board of directors and composition of independent commissioners. The financial performance of banking companies is measured by Return on Equity (ROE). The population used in this research was the Influence of the Implementation of Good Corporate Governance on Financial Performance (Studies Listed on the Indonesian Stock Exchange 2017-2020) totaling 626. The sample selection technique used purposive sampling so that 52 companies were obtained. The type of data used is secondary data. The data analysis technique in this research uses multiple linear regression analysis. The results of this research partially show that the percentage of institutional ownership, composition of the board of directors, and composition of independent commissioners do not have a significant effect with a negative coefficient on ROE. Meanwhile, simultaneously the percentage of institutional ownership, composition of the board of directors and composition of independent commissioners have a significant effect on ROE with a positive coefficient.